2022
DOI: 10.3389/fmars.2022.917857
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and Clinical Studies of Sea Cucumber-Derived Bioactives for Human Health and Nutrition From 2012-2021

Abstract: Sea cucumbers are amongst the highest value seafoods available commercially, especially in the south-east Asian region, primarily due to their nutritional and health benefits as applied in Traditional Chinese Medicine. While the majority of studies for nutritional products derived from sea cucumber compounds have been conducted in vitro, the number of in vivo and evidence-based human clinical studies are limited. This review has critically assessed the advances in in vivo and clinical studies of sea cucumber-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 109 publications
(197 reference statements)
1
4
0
Order By: Relevance
“…In addition to being valuable marine commodities, sea cucumbers are a significant source of medicine ( Zhao et al, 2018 ). They are used in traditional Chinese medicine and are thought to have therapeutic capabilities, to treat conditions such as arthritis, high blood pressure, asthma, cancer, frequent urination, and impotence ( Guo et al, 2015 ; Pangestuti & Arifin, 2018 ; Liang et al, 2022 ). They have extensive uses in the biomedical industry, where they are believed to possess therapeutic capabilities ( Zohdi et al, 2011 ) and numerous active ingredients, including polysaccharides, peptides, proteins, lipids, ( Janakiram, Mohammed & Rao, 2015 ), collagen, gelatine, saponins and acid mucopolysaccharides ( Kariya et al, 2004 ; Lu et al, 2010 ; Zhou, Wang & Jiang, 2012 ; Yang, Hamel & Mercier, 2015 ).…”
Section: Survey Methodologymentioning
confidence: 99%
“…In addition to being valuable marine commodities, sea cucumbers are a significant source of medicine ( Zhao et al, 2018 ). They are used in traditional Chinese medicine and are thought to have therapeutic capabilities, to treat conditions such as arthritis, high blood pressure, asthma, cancer, frequent urination, and impotence ( Guo et al, 2015 ; Pangestuti & Arifin, 2018 ; Liang et al, 2022 ). They have extensive uses in the biomedical industry, where they are believed to possess therapeutic capabilities ( Zohdi et al, 2011 ) and numerous active ingredients, including polysaccharides, peptides, proteins, lipids, ( Janakiram, Mohammed & Rao, 2015 ), collagen, gelatine, saponins and acid mucopolysaccharides ( Kariya et al, 2004 ; Lu et al, 2010 ; Zhou, Wang & Jiang, 2012 ; Yang, Hamel & Mercier, 2015 ).…”
Section: Survey Methodologymentioning
confidence: 99%
“…scabra) is a species of sea cucumber, an invertebrate marine animal mostly found in the Indo-Pacific region. Sea cucumber-derived bioactive compounds have been reported to exhibit promising medical potentials, including antihyperlipidemic, anticancer, anti-inflammation, antioxidant, antihypertension, anticoagulant, immunomodulatory, and neuroprotective treatments . The beneficial compounds in sea cucumbers are reported to include fucosylated chondroitin sulfate, triterpene glycoside (saponins), glycosaminoglycan, phospholipids, peptides, phosphatidylcholines, collagen, phenols, amino acids, calcium, omega-6, and omega-9 .…”
Section: Introductionmentioning
confidence: 99%
“…Sea cucumber-derived bioactive compounds have been reported to exhibit promising medical potentials, including antihyperlipidemic, anticancer, anti-inflammation, antioxidant, antihypertension, anticoagulant, immunomodulatory, and neuroprotective treatments . The beneficial compounds in sea cucumbers are reported to include fucosylated chondroitin sulfate, triterpene glycoside (saponins), glycosaminoglycan, phospholipids, peptides, phosphatidylcholines, collagen, phenols, amino acids, calcium, omega-6, and omega-9 . These constituents and their health-promoting actions render sea cucumbers being a potential target for intense biomedical research as well as for food in the Asian region .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sea cucumber, a traditional tonic food, is characterized by high protein and low fat, thereby peptides obtained from enzymatic hydrolysis of sea cucumbers are being studied ). We found that sea cucumber peptides (SCPs) have antioxidant, antidiabetic, immunomodulatory, anti-cancer, anti-aging, neuroprotective, and trace element chelation functions (Lu et al 2022) which makes them potentially of great application in highly effective antifatigue products and skin care products, etc (Liang et al 2022). However, SCPs usually have a heavy shy odor which directly affects their application prospect, so how to remove the shy odor e ciently and green becomes very important.…”
Section: Introductionmentioning
confidence: 99%